The perception and attitude of South Sulawesi youth towards the impacts of uang panai: a pilot study - ., Nurmiati; Mohamad Diah, Nurazzura (Universiti Sultan Zainal Abidin ( UNISZA ), 2018)
The focus of this study is to investigate the perception and attitude of South Sulawesi youth on the impacts of uang panai. For this pilot study, a self-administered survey questionnaire was distributed to 50 South Sulawesi youth. The respondents are South Sulawesi youth whose age is between 20-36 years old. Some of them have completed their tertiary studies while others are currently pursuing theirs. All data were analyzed using the Statistical Package for Social Sciences (SPSS) version 24. The results show that the correlation between South Sulawesi youth’s perception and the impacts of uang panai and the correlation between the attitudes of South Sulawesi youth towards uang panai are both moderately significant. The findings confirm that uang panai is one of the core elements to legalize marriage and must be performed by couples who intend to get married in South Sulawesi. Uang panai is indeed a South Sulawesi identity and this study endorses previous studies on the same topic.